Academic and Student Affairs in Collaboration: Creating a Culture of Student Success: By Mitchell A. Levy and Bernard A. Polnariev, editors, 2016. New York, NY: Routledge, 166 pages, ISBN 9781138913301, Paper, 39.62. Issue 4 (2nd October 2017) - Eberhardt, David
Abstract: Collaboration among academic affairs and student affairs occupies significant space in the higher education literature and remains an important topic discussed at many professional meetings. Seeking to partner with faculty in support of students has been a longstanding principle among student affairs practitioners in particular. The editors of Academic and Student Affairs in Collaboration argue past partnerships have often been ineffective, however. They and the various authors of this volume share ways they believe that authentic collaboration can occur and how it can be assessed to ensure and enhance student success outcomes. They build on past literature to argue that success remains possible through a collective and singular goal of student success, which fosters authentic collaboration among diverse areas. Readers interested in student success outcomes, retention and graduation in particular but also in other vital areas such as civic engagement, intercultural understanding, and ethical and personal development, will likely find the work beneficial.